Cobalt‐Based MOF‐Derived CoP/Hierarchical Porous Carbon (HPC) Composites as Robust Catalyst for Efficient Dehydrogenation of Ammonia‐Borane - Ma, Xiao‐Chen; He, Yue‐Yue; Zhang, Dai‐Xue; Chen, Min‐Jie; Ke, Shan‐Chao; Yin, Yi‐Xia; Chang, Gang‐Gang (ChemistrySelect (Weinheim), 2020)
Transition‐metal phosphides (TMP), particularly cobalt phosphide (CoP) has drawn considerable attention in heterogeneous catalysis during the past few years due to their robust stability, corrosion resistance and low cost. In this work, a series of hierarchically porous carbon supported non‐precious CoP NPs by using Co–MOF‐74 as self‐sacrificed templates have been synthesized through a stepwise calcinations and phosphorization method. The catalytic performance of the resulted CoP@HPC−T composites toward the hydrolytic dehydrogenation of ammonia‐borane (AB) has been systematically investigated, of which, the resultant CoP@HPC−T calcinated at 500 °C showed the best catalytic performance with a TOF value of 27.7 min−1, and relatively low activation energy (42.55 kJ/mol) even comparable to those reported noble metal catalysts. Furthermore the robust structure of CoP@HPC−T compared to the Co@HPC−T counterpart in the recycle tests, demonstrating their great potential for practical application. The hierarchically porous carbon supported non‐precious CoP NPs by using Co–MOF‐74 as self‐sacrificed templates have been synthesized through a stepwise calcinations and phosphorization method. The resulted CoP@HPC−T composites toward the hydrolytic dehydrogenation of AB showed the remarkable catalytic performance.